Towards health impact assessment of drinking-water privatization: the example of waterborne carcinogens in North Rhine-Westphalia (Germany) - Fehr Rainer; Mekel Odile; Lacombe Martin; Wolf Ulrike (The World Health Organization, 2003)
Worldwide there is a tendency towards deregulation in many policy sectors - this, for example, includes liberalization and privatization of drinking-water management. However, concerns about the negative impacts this might have on human health call for prospective health impact assessment (HIA) on the management of drinking-water. On the basis of an established generic 10-step HIA procedure and on risk assessment methodology, this paper aims to produce quantitative estimates concerning health effects from increased exposure to carcinogens in drinking-water. Using data from North Rhine-Westphalia in Germany, probabilistic estimates of excess lifetime cancer risk, as well as estimates of additional cases of cancer from increased carcinogen exposure levels are presented. The results show how exposure to contaminants that are strictly within current limits could increase cancer risks and case-loads substantially. On the basis of the current analysis, we suggest that with uniform increases in pollutant levels, a single chemical (arsenic) is responsible for a large fraction of expected additional risk. The study also illustrates the uncertainty involved in predicting the health impacts of changes in water quality. Future analysis should include additional carcinogens, non-cancer risks including those due to microbial contamination, and the impacts of system failures and of illegal action, which may be increasingly likely to occur under changed management arrangements. If, in spite of concerns, water is privatized, it is particularly important to provide adequate surveillance of water quality.